Field Measurement and Analysis of Small-Scale Solar Water Heating Systems in Urban Residential Areas (International Journal of Engineering and Computer Science, 2025)
This study presents field measurements and analysis of small-scale solar water heating (SWH) systems installed in urban residential areas of Tehran, Iran. Over a 12-month period from January to December 2024, data were collected from 10 residential units equipped with flat-plate collectors and thermosyphon systems. Key performance indicators, including thermal efficiency, solar fraction, and energy savings, were evaluated under varying urban conditions such as shading from high-rise buildings and ambient temperatures ranging from -5°C to 40°C. Results indicate an average annual thermal efficiency of 58%, with peak efficiencies reaching 75% during summer months. The systems provided up to 70% of hot water needs, reducing fossil fuel consumption by approximately 2,500 kWh per household annually. Economic analysis shows a payback period of 5-7 years, considering local subsidies. Challenges like dust accumulation and urban heat island effects were quantified, leading to recommendations for optimized designs in dense urban environments.